DEVELOPMENT OF ALGORITHM OF THE BUILD-UP OF A TEACHING ESTABLISHMENT PROFILE ON THE BASIS OF RESEARCH AND COMPETITIVE APPROACH - Y. Danilina (Вестник университета)
The article provides the reasons which allow to formulate the necessity of the build-up of the resource profile of a teaching establishment which is to mirror a system of network relationships with all stakeholders, as well as to characterize a specific status of each teaching establishment in educational and scientific environment. In order to build up a resource profile a universal algorithm is suggested, this algorithm will enable to carry out actions step by step to form the resource profile. The formation of the algorithm is based on the conceptions of resource-competence and stakeholders management, besides, current developments of domestic specialists in forming a strategy for interaction between an educational establishment and its stakeholders are taken into account. It is proved that as the suggested algorithm is being realized, there will be inconsistencies in resources, capabilities and competencies of a teaching establishment which are to lay the foundation of all directions to modernize a teaching establishment.